Leveraging allelopathic plant interactions for sustainable natural pest control - Kumar, Yengkhom Bijen; Singh, N Raju; Sangma, Rumki; M, Prabha; Hazarika, S (Indian Farming, 2024)
As the world seeks to transition towards more sustainable agricultural and ecological practices, there is a growing interest in innovative pest control methods that minimize environmental harm and reduce reliance on chemical pesticides. One promising avenue is the use of allelopathic plant interactions, a phenomenon where certain plants release bioactive compounds that influence the growth and development of neighbouring plants. This article explores the principles and potential applications of allelopathy in the context of sustainable natural pest control. It delves into the mechanisms by which allelopathy can deter and manage pests, highlighting the multifaceted approach it offers. The article also discusses the environmental and ecological benefits of adopting allelopathic pest control, emphasizing the need for further research and practical implementation to fully realize its potential.